2015
DOI: 10.4172/2167-7964.1000196
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Antigen-Specific Cytotoxic T Lymphocytes by Chemoradiotherapy in Patients Receiving Wilms? Tumor 1-Targetted Dendritic Cell Vaccinations for Pancreatic Cancer

Abstract: Despite recent advances in cancer treatment, the prognosis of pancreatic cancer (PC) remains poor. Dendritic cells (DCs) play a central role in acquired immunity; therapeutic DC vaccinations have recently been developed for advanced PC. Here we present two cases of PC: inoperable PC localized to the pancreatic head (Case 1, stage IV) and local recurrence complicated by distant metastases following resection of the pancreas body and tail (Case 2, stage III). Both patients received DC vaccinations pulsed with hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It has also been reported that WT1 antigen expression in pancreatic cancer cell lines is increased by GEM treatment (65). Initial radiotherapy with additional chemotherapeutic drugs acting through their off-target effects may have accelerated the development of acquired cancer immunity and induced antigen-specific CTLs in patients receiving WT1-targeted DC vaccinations (47). Therefore, DC vaccines in combination with chemotherapy and radiotherapy should promote treatment efficacy against advanced disease.…”
Section: Vaccination Technology For Pediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that WT1 antigen expression in pancreatic cancer cell lines is increased by GEM treatment (65). Initial radiotherapy with additional chemotherapeutic drugs acting through their off-target effects may have accelerated the development of acquired cancer immunity and induced antigen-specific CTLs in patients receiving WT1-targeted DC vaccinations (47). Therefore, DC vaccines in combination with chemotherapy and radiotherapy should promote treatment efficacy against advanced disease.…”
Section: Vaccination Technology For Pediatric Patientsmentioning
confidence: 99%
“…Sipuleucel-T (Provenge ® ) is a US Food and Drug Administration-approved autologous DC-based immunotherapy for men with metastatic hormonerefractory prostate cancer, which provides a new treatment option for patients with this type (36)(37)(38). DC vaccines primed with HLA class I-/II-restricted WT1 peptides (WT1-DC) have been determined to be safe and feasible, with few adverse reactions reported by patients with advanced cancers, including lung, breast, stomach, biliary tract, pancreas, ovary, and even high-grade glioma (39)(40)(41)(42)(43)(44)(45)(46)(47). Clinical studies have indicated that the efficacy of DC vaccination may be enhanced by the off-target effects of chemotherapeutic drugs (39)(40)(41)(42)(43)(44)48) and chemoradiotherapy (47,49,50), suggesting a survival benefit in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy can also enhance the expression of HLA class I on the surface of cancer cells, boosting the recognition and killing of irradiated cancer cells through T cells and NK cells [24]. DCs in combination with chemoradiotherapy may accelerate the development of acquired cancer immunity to induce antigen-specific cytotoxic T lymphocytes (CTLs) [25,26]. Chemoradiotherapy induce immunogenic cell death, which could trigger T-cell immunity mediated by high-mobility group box 1 protein in patients with oesophageal squamous cell cancer [27].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the clinical efficacy is more evidently demonstrated by the delayed separation of the survival curve with a benefit in terms of prolonged overall survival (OS) [ 31 , 32 ]. The efficacy of DC vaccination may be enhanced by off-target effects of chemotherapeutic drugs, radiotherapy, and chemoradiotherapy [ 33 , 34 , 35 ]. The combination of chemotherapy and/or radiotherapy has been investigated in addition to the period required for adaptation.…”
Section: Introductionmentioning
confidence: 99%